Paraaortic Lymph Node Involvement among Indonesian Women with Cervical Cancer - Pradana, Wisniardhy Suarnata; Aslam, Achmad Bayhaqi Nasir; Nugroho, Rafiq Sulistyo; Setijowati, Nanik; Siswidiyati, Siswidiyati (Indonesian Journal of Cancer, 2025)
Background: Incorporating para-aortic irradiation alongside standard pelvic irradiation has shown potential benefits for treating cervical cancer. However, its efficacy remains debatable due to insufficient information about paraaortic lymph node (PALN) involvement among Indonesian women. This study aims to determine the incidence of PALN and assess potential influencing factors, such as age, characteristics of the cervical mass (size and surrounding tissue involvement), and histopathology.Method: This study was a retrospective analytic observational study with a cross-sectional design, examining PALN involvement and localization in patients’ computed tomography (CT) scans before radiotherapy in 2023. The inclusion criteria are cervical cancer patients who were confirmed through a histopathological examination and underwent an abdominal CT scan before radiotherapy from January to December 2023. The exclusion criteria are cervical cancer patients accompanied by other primary tumors and patients who have undergone hysterectomy. The CT scans were conducted using a 16-slice Canon Aquilion from T12 to the proximal third with a 3 mm slice thickness. Factors influencing the risk of PALN involvement were analyzed using chi-square tests.Results: Eighty-seven eligible patients were analyzed. The median age was 52.26 years, with 72.4% at stage IIIB, 77% diagnosed with squamous cell carcinoma, and 89.7% with a mass size of over 4 cm. Almost all patients exhibited surrounding tissue involvement. 32.2% of patients had paraaortic lymph node involvement, with the majority (70.7%) located in the left para-aortic region and ≤ 5 mm from the aorta. There was no significant relationship between PALN involvement and age, characteristics of the cervical mass, or histopathology type.Conclusion: In a population of locally advanced cervical cancer, almost one-third of patients showed PALN involvement. Implementing PALN radiation in this population could potentially enhance outcomes, irrespective of the patient’s age, characteristics of the cervical mass, or histopathology results.